Equivalent Intrinsic Noise, Sampling Efficiency, and Contrast Sensitivity in Patients With Retinitis Pigmentosa - McAnany, J. Jason (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. To determine the relationships among equivalent intrinsic noise (N(eq)), sampling efficiency, and contrast sensitivity (CS) in patients with retinitis pigmentosa (RP), where N(eq) is an estimate of the amount of noise within the visual pathway and sampling efficiency represents the subject's ability to use stimulus information optimally. METHODS. Participants included 10 patients with RP aged 10 to 54 years, who had visual acuities of 20/40 or better, and 10 visually normal control subjects aged 22 to 65 years. CS was measured for 2-cycles-per-degree Gabor patch targets presented in the absence of noise (CS(0)) and in five levels of noise spectral density. Data were fit with a standard linear amplifier model, which provided estimates of N(eq) and sampling efficiency. RESULTS. CS(0) for the patients ranged from normal to as much as a factor of 3 below the lower limit of normal. All 10 patients had abnormally high N(eq), including two patients with normal CS(0). In comparison, only two patients had lower-than-normal sampling efficiency, and these two patients also had below-normal CS(0). Log CS(0) for the patients was correlated significantly with log N(eq) (r = −0.80, P < 0.05), but not with log efficiency (r = 0.54, P = 0.11). CONCLUSIONS. Low CS was associated with elevated intrinsic noise in this group of RP patients, but even patients with normal CS had elevated noise levels. The results suggest that CS measurement in both the presence and absence of luminance noise can provide important information about visual dysfunction in RP patients.